Aetiologies of acquired deafblindness in a national sample. (May 2018) - Teglbjærg, Jonas Henau; Hovaldt, Hanna Birkbak; Lehane, Christine; Dammeyer, Jesper
The present study provides an overview of aetiologies and co-morbidities of acquired deafblindness in a Danish national sample of 514 individuals above 50 years of age identified with acquired deafblindness. Information was obtained from a survey and a register. The most frequent aetiology of vision loss was age-related macular degeneration (55.4%). The most frequent aetiology of hearing loss was presbycusis (53.7%). The most frequent aetiology of acquired deafblindness was the combination of age-related macular degeneration and presbycusis (41.5%). However, among the younger participants (50–59 years of age), Usher syndrome was the most common aetiology (62.5%). The aetiologies of acquired deafblindness are many and constituted by several different combinations of hearing and vision loss aetiologies. The most frequent aetiologies are age related.